Os municípios e a instrução primária no Estado de Goiás: as singularidades de Rio Verde (1889-1918) - Silva, Maria Aparecida Alves (2018)
This thesis results from a research on Education, whose line is History and Historiography of Education and has, as object of study, the primary public education in the State of Goiás, from 1889 to 1918. For this purpose, we delimit, for a more detailed analysis, the participation of municipalities in the process of organization of primary education, and we elected the municipality of Rio Verde as the locus for research into this process. The guiding question of this research is to verify how the process of organization of the primary public education in the State of Goiás occurred in the period referred to. In face of this problem, other questions arise: How did state legislation regulate the participation of municipalities in relation to primary education? What is the position of the political elites of Goiás in relation to this type of education? How did the municipalities participate in the Goiás effort for education? How did Rio Verde / GO organize the primary education in this period? And to what extent has such an organization shared perspectives similar to those that guided the national debate about Brazilian education? What are the initiatives of the rio-verdense government aimed at this type of education? As general objective, we seek to analyze the process of organization of primary public education in the State of Goiás, in the period mentioned above, taking as reference the municipality of Rio Verde / GO. Our specific objectives were: to verify how the state legislation regulated the participation of municipalities in relation to primary education; to verify the importance that every oligarchy in Goiás attributed to primary education and what was their position about the responsibility of municipalities for the process of creation and maintenance of schools; to analyze the rio-verdense government initiatives aimed at primary education, verifying how the political elite appropriated such responsibility. This is a qualitative documentary research, in which the primary public education in the State of Goiás is analyzed under the bias of Cultural History. For the writing of the historical narrative, the following sources were used: Municipal and State Legislation, Messages of the Governors / Presidents of the State of Goiás, Journals, Minutes of the Municipal Council of Rio Verde, among others. Through analysis of these sources, we verified that, in Goiás, at the beginning of the Republic, there was state action for the promotion of primary education, as well as municipal initiatives, as evidenced by the municipality of Rio Verde. Thus, in places where the state did not create and maintain primary schools, the municipality assumed responsibility. We also found that educational laws were unstable until 1918, since they sometimes left primary education under the responsibility of municipalities, and sometimes, in a complementary way, under the responsibility of state government. Moreover, these legislations were marked by the tensions between the state oligarchies and the colonelism established in the municipalities, since each group that was in power sought the opportunity of achieving personal goals. At local level, we found that the city of Rio Verde / GO, anchored in Law no. 186, dated August 13th, 1898, assumed responsibility for primary education on June 2nd, 1899. Since then, the discussion and approval of laws aimed at municipal education have been constant in the Municipal Council, as well as the promulgation of decrees by the municipal intendant Thus, when it assumed responsibility over primary education, the municipality demarcated its jurisdiction, protected its right of autonomy and sought to create municipal identity.